全球化脈絡下的教育課題：全球教育 The Educational Topic Within the Globalizing Context Global Education - 顏佩如 Pey-Ru Yen (Higher Education Foundation, 2005)
本文首先談及全球化與反全球化思潮及活動，談及「全球教育」是化解全球下議題的要件，並陳述全球教育在歷史發展中遭受政治與宗教的挑戰與回應；第二，筆者將談及全球教育的發展，包括全球教育概念的分析、比較、遷移、發展分期、我國研究發展，以及概念轉變的綜合評析；第三，談到全球教育觀點的變遷與國際概況；第四，談到全球教育的「世界－本土」關係、全球教育的責任、哲理建構的探究等，最後提出全球教育的理想與展望。 This article mainly explored the thoughts and activities of the globalization and anti-globalization, and talked about that "global education" could be one of the essential factors to bring reconciliation among the arguments and issues. Then, the composer indicated the challenge and the responses of the global education which was subjected to the politics and religions during the development of human history. Secondly, the researcher discussed the development of global education which included the analysis, the comparison, the transition, development stages, research development of Taiwan and mainland China, and the change and synthetic analysis of its concepts. Thirdly, this paper illustrated the transition of the points and the brief profile of the international situations of "global education". Fourthly, the author generalized the relationship of "world-local" of global education, including the basic assumption and premise, the responsibilities, the inquiry of the rationale construction and etc. of "global education." Finally, the writer provided the ideal and the prospect of the global education.